Analysis of the influence of Entrepreneurial and Networking Competitive Advantage on Business Performance with Use of Digital Marketing as a Moderating on Agricultural SME’s in Makassar City - Fitriany Fitriany; Sri Endarti Halim; Muh Akil Rahman; Rachman Suwandaru (Postgraduate, University of Mataram, 2023)
The purpose of this research is to (1) determine the analysis of entrepreneurial influence Networking, Competitive Advantage influences Agriculture SME’s Business Performance in Makassar City (2) To analyze whether Digital Marketing is able to moderate the influence of Entrepreneurial Networking, Competitive Advantage on Performance Makassar City Agriculture SME’s Business. This type of research is causality. Research population This is a total of 86 Agriculture SME actors in Makassar City. Testing research data using a measurement model or often called outer models and structural models (structural models) or often called inner models, and effect size for moderating variables. The results of this research prove that (1) Entrepreneurial Networking, Competitive Advantage has a positive and significant effect on Makassar City Agriculture SME’s Business Performance (2) Digital Marketing cannot moderating the influence of Entrepreneurial Networking, Competitive Advantage on Agriculture SME’s Business Performance in Makassar City